Pelestarian Nasi Tumpang Sebagai Identitas Kuliner Lokal Masyarakat Boyolali - Hartini, Sri (Innovative: Journal Of Social Science Research, 2021)
Nasi Tumpang is a typical culinary food that has been a tradition passed down from generation to generation for the Boyolali people. This research aims to determine efforts to preserve Nasi Tumpang as the local culinary identity of the Boyolali community. The research results show that: 1) The Boyolali community has a strong urge to learn about the processing of Nasi Tumpang; 2) Passing on knowledge to the next generation; 3) Making rice as a menu option for banquets at events held by the Boyolali community, for example family events, traditional events, and community gathering events; 4) Utilizing the role of communication media in supporting efforts to preserve Nasi Tumpang.